Synergism between dengue and COVID-19: evidence or occasional? - Labes, Luiza; Trentin-Bordignon, Natalia Cristina; Gondak, Rogério (Journal of Oral Diagnosis, 2021)
The global spread of the new coronavirus has brought to light several discussions regarding infectious agents and ways of transmission of viral diseases. In South America, cases of misdiagnosis between COVID-19 and dengue have been reported. This letter aimed to expose the main symptoms that confuse health professionals for the diagnosis of the acute phases of these diseases. Due to the presence of synergistic symptoms between COVID-19 and dengue in their acute phase, we sought to report marked differences between both infectious agents, based in studies published in the literature. Considering the double pandemic of COVID-19 and dengue and its impact either in the basic sanitation and the public health system, the development of an effective rapid virus tests is mandatory and useful to guide the adequate treatment of the patient. Health professionals should be alert for the synergistic symptoms of these infectious diseases. Further studies and development of more accessible and effective rapid tests are encouraged for COVID-19 and dengue.